Effect of in vitro environmental conditions on the biological attributes of termite Odontotermes wallonensis - Prahlad, Bhurli; B, Chimkod V (International Multidisciplinary Research Journal, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> An investigation was carried out to assess and understand the effect of moisture, temperature and nutrients on the laying of eggs, hatching of nymphs and development of adults of a termite Odontotermes wallonensis. The results of the investigation clearly reveals that, all these environmental factors monitored and regulated in-vitro conditions were highly interdependent and effective individually. 40% moisture content and 200C temperature were found to be quite effective on the prominent egg laying attribute of Odontotermes wallonensis. However, during hatching of nymphs by the eggs 60% moisture content and 400C temperature were proved to be optimum. Development of adults from the nymphs of Odontotermes wallonensis was very healthy at 40% moisture content and 200C temperature. Further, the red soil of natural mound was found to be better nutrient, when compared to the fine saw mill powder for all the three biological attributes of Odontotermes wallonensis.